Natural convection in an open ended nanofluid filled cavity with fins in the presence of partial magnetic field and thermal radiation - Geridonmez, Bengisen Pekmen; Öztop, Hakan Fehmi (Wiley, 2021)
In this paper, the effect of uniform partial magnetic field is studied on natural convection flow in an open ended square cavity considering thermal radiation and the presence of two fins as well as a uniform partial magnetic field. The polyharmonic spline radial basis function pseudo-spectral method is implemented on nonuniform grids for numerical simulation of the problem. The dimensionless governing equations are adopted in stream function-vorticity formulation. In the geometry of the problem as a unit square cavity, the right wall is open, the top wall is the cold wall including a cold fin, the bottom wall is the hot wall involving a hot fin, and the left wall is adiabatic. The uniform partial magnetic field is assumed to be vertically applied. The presence of both fins and the partial magnetic field reduces the convective heat transfer. The rise in both Hartmann number and radiation parameter suppresses the temperature gradient along the right bottom part of the cavity. Fins and partial magnetic field can be used as controlling structures for fluid flow and heat transfer in such a Rayleigh-Benard type problem.
Keywords: natural convection flow; partial magnetic field; radial basis functions; thermal radiation